Cortical correlate of the Piper rhythm in humans. - Brown, P; Salenius, S; Rothwell, J; Hari, R (1998)
Cortical correlate of the Piper rhythm in humans. J. Neurophysiol. 80: 2911-2917, 1998. The electromyogram (EMG) of healthy humans demonstrates a tendency to rhythmic oscillations at around 40 Hz (the Piper rhythm) during strong voluntary contraction. Why motor units should discharge synchronously locked to such a high-frequency is unclear. We recorded whole scalp magnetoencephalographic (MEG) signals simultaneously with surface EMG from 10 healthy subjects. In eight subjects, coherence and time domain analyses demonstrated correspondence between the MEG signal, originating near or in the hand region of the motor cortex, and the 35- to 60-Hz EMG recorded during repeated maximal isometric contractions of the contralateral forearm extensor muscles. Three of these subjects also showed similar coherence during isometric contractions of moderate strength and slow extension movements of the wrist. In addition, coherence and time domain analyses demonstrated correspondence between the MEG signals originating near or in the foot area of the motor cortex and EMG recorded during repeated maximal isometric contractions of the contralateral tibialis anterior muscle in the 30- to 60-Hz range. Most important, the frequency at the peak of the coherence spectrum differed between forearm and leg by as much as 10 Hz in the same subject. In contrast, the peak of the coherence spectrum occurred during sustained weak contraction in the 20- to 30-Hz range similarly for both forearm and foot. The lag between EMG and MEG activity in the leg was approximately 15 ms greater than that seen in the forearm, an interval appropriate for conduction in fast pyramidal pathways. It is concluded that the Piper rhythm in muscle may be driven by a comparable oscillatory activity in the contralateral motor cortex. This cortical rhythmicity can be picked up in several types of movement and seems distinct from the 20- to 30-Hz rhythmicity recorded during weak sustained contractions.